M1 is not M1 in ischemic stroke: the disability-free survival after mechanical thrombectomy differs significantly between proximal and distal occlusions of the middle cerebral artery M1 segment. (24th June 2014) - Behme, D; Kowoll, A; Weber, W; Mpotsaris, A
Abstract : Aims: Recent recommendations on the designation of target artery lesions in acute ischemic stroke include the anatomical differentiation between a proximal and a distal occlusion site of the M1 segment of the middle cerebral artery (MCA). The aim of this study was to evaluate whether these occlusion types differ in terms of a disability-free (modified Rankin Scale (mRS) 0 or 1) clinical outcome at 90 days. Methods: A retrospective analysis was performed of all patients with MCA M1 occlusions who had a successful revascularization result after mechanical thrombectomy between October 2009 and September 2013 and for whom follow-up at 90 days was available. Imaging data were regraded and re-evaluated according to the modified Thrombolysis In Cerebral Infarction (mTICI) scale and the respective vessel occlusion site definitions. Outcome measures included National Institutes of Health Stroke Scale (NIHSS), mRS, Alberta Stroke Program Early CT Score (ASPECTS) scoring and procedural timings. Results: 62 patients were successfully recanalized; follow-up at 90 days was available for 42/62 patients (68%). There were proximal MCA occlusions in 24/42 patients (57%) and distal occlusions in 18/42 (43%). Baseline NIHSS, ASPECTS, procedural timings and final mTICI scores did not differ significantly between proximal and distal M1 occlusions. There was a statistically significant difference between proximal and distal M1 occlusions regarding a disability-free early outcome (mRS 0 or 1) at discharge (p=0.03) and at 90 days (p=0.04). Conclusions: Proximal occlusions of the M1 segment of the MCA incorporating the lenticulostriate perforators are associated with a poorer clinical outcome than distal M1 occlusions that spare these perforators. Involvement of these perforators might become an additional predictor of clinical outcome after mechanical thrombectomy in ischemic stroke.